The poetry of N.H. Brettell : a critical edition - Hacksley, Reginald Gregory (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2006)
This thesis presents for the first time a critical reading edition of all known poems by N. H. Brettell. It makes no claim to being definitive, nor does it attempt to establish a final text. It represents merely the best thinking of the editor. Brettell printed and circulated his poetry primarily in hand-made illustrated volumes in a process reminiscent of the scribal publication of the seventeenth century. Only 137 of his 206 extant poems were commercially published during his lifetime. In this study all known printed versions of Brettell's poetry whether in privately printed or commercially published form were examined. All variant readings were recorded and are shown. Wherever possible the relationships between texts are also noted. The poems in this edition are ordered in each case according to the version in the latest datable privately produced collection. The commentary and critical introduction were compiled with the general reader in mind. No previous familiarity with southern African fauna and flora is assumed: animals, birds and insects are described and their scientific names supplied. Expressions current in ordinary British or South African English and present in non-specialist dictionaries are not glossed, but archaic and dialectal forms felt to require explication are briefly explained. So too are less familiar South African dialectal expressions which have been assimilated into the South African English lexicon. Intertextual, Christian and mythological references, both African and Western, are annotated in an attempt to make such references accessible to readers who may not share Brettell's cultural background. The intention is to close the changing distance between the text and the audience. An essay discussing the merits, potential and limitations of electronic scholarly editing is included as part of the textual introduction. A CD-Rom containing Brettell's watercolour illustrations in his privately produced collections and audio-clips of him reading his poetry accompanies this thesis.
Keywords: Brettell, N H -- Criticism and interpretation; South African poetry (English) -- History and criticism